2000
DOI: 10.1161/01.str.31.2.410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poststroke Pyrexia on Stroke Outcome

Abstract: Background and Purpose-The effect of pyrexia on cerebral ischemia has been extensively studied in animals. In humans, however, such studies are small and the results conflicting. We undertook a meta-analysis using all such published studies on the effect of hyperthermia on stroke outcome. Methods-Three databases were searched for all published studies that examined the relationship of raised temperature after stroke onset and eventual outcome. Combined probability values and odds ratios were obtained. A hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
186
2
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(207 citation statements)
references
References 33 publications
(47 reference statements)
8
186
2
11
Order By: Relevance
“…4,5 Furthermore, several studies have shown that elevated body temperature (which often results from infection) early after ischemic stroke is associated with severe neurological deficit and a poor outcome. [6][7][8][9] Indeed, pneumonia and urinary tract infection (UTI) are among the most frequent individual infective complications encountered following acute stroke. 1,10 Given the aforementioned, heightened awareness of infective complications during stroke hospitalization is underscored in national guidelines, and antibiotics to treat infection after stroke are strongly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Furthermore, several studies have shown that elevated body temperature (which often results from infection) early after ischemic stroke is associated with severe neurological deficit and a poor outcome. [6][7][8][9] Indeed, pneumonia and urinary tract infection (UTI) are among the most frequent individual infective complications encountered following acute stroke. 1,10 Given the aforementioned, heightened awareness of infective complications during stroke hospitalization is underscored in national guidelines, and antibiotics to treat infection after stroke are strongly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] It is widely accepted from experimental and clinical studies that hyperthermia increases infarct volume and worsens functional outcome. 4,[7][8][9][10] Hyperthermia can influence the evaluation of neuroprotective compounds in experiments in which the suture occlusion model is used. 11 The recently developed "macrosphere model" is a new intravascular technique for permanent MCAO in rats that, in contrast to the suture model, does not cause artificial hyperthermia.…”
mentioning
confidence: 99%
“…In recent years, the prognostic importance of body temperature during the acute phase of ischemic stroke has been increasingly recognized. Several clinical studies have consistently shown that in the early phase after stroke, fever (>37.5°C) is very common, occurring in up to 61 % of patients, increases with the severity of stroke, and is a strong predictor of an unfavorable outcome [25][26][27]. A multitude of different biochemical and inflammatory mechanisms responsible for the detrimental effects of fever during the acute phase of stroke have been identified, including 1) enhanced release of excitatory neurotransmitters; 2) increased metabolic demands; 3) exaggerated free oxygen radical production; 4) increased breakdown of the blood-brain barrier; 5) elevated rate of potentially damaging depolarizations in the ischemic penumbra; 6) impaired recovery of energy metabolism and enhanced inhibition of protein kinases; and 7) worsening of cytoskeletal proteolysis [28].…”
Section: Rationale Behind Prophylactic Antibiotic Therapy In Strokementioning
confidence: 99%